Immune checkpoint inhibitors in older adults with melanoma or cutaneous malignancies: The Wilmot Cancer Institute experience. Issue 3 (April 2020) - Archibald, William J.; Victor, Adrienne I.; Strawderman, Myla S.; Maggiore, Ronald J.
Abstract: Objectives: The purpose of this study was to explore the associations between age and frailty with immune-related adverse events (irAEs) among patients with cutaneous malignancies receiving immune checkpoint inhibitor (ICI) therapy. Methods: A retrospective review of all patients receiving ipilimumab, nivolumab, or pembrolizumab for treatment of cutaneous malignancies at the Wilmot Cancer Institute between 1 Jan 2011 and 3 Apr 2017. Results: A total of 120 patients (age <70 N = 68, age ≥70 N = 52; range, 26–93) were identified. 44.1%[95%CI:32–57%] of patients age <70 and 31.4%[95%CI:19–46%] of patients age ≥70 experienced ≥1 irAE on 1st line ICI therapy (P = 0.158). A total of 3 adults died of irAEs (2 age ≥70; 1 age <70). Patients ≥70 were more frequently treated with anti-PD-1 monotherapy than dual checkpoint blockade or ipilimumab (P < 0.01) in the first line setting. Among patients on first line anti-PD-1 monotherapy for cutaneous melanoma, 21 were age <70 and 20 were age ≥70, with similar observed rates of irAEs (52.4%[95%CI 29.8–74.3] and 63.2%[95%CI 38.4–83.7]). Indirect frailty markers in patients age ≥70 such as having fallen in the prior six months, ECOG PS ≥2 or Charlson comorbidity scores ≥11 experienced similar rates of response and toxicity. Among 9 patients with a PS = 3, 8 died, 6 due to progressive disease. No deaths due to irAEs occurred in this frail subgroup. Conclusion: Anti-PD-1 monotherapy for older adults with cutaneous malignancies have similar response and irAE rates when compared to those of younger patients. Deaths from disease progression were more frequent than those from toxicity in both age subgroups.